Outcomes with frontline immune checkpoint inhibitors among individuals with BRAF-mutant non-small cell lung cancer - Marin-Acevedo, Julian A.; Thapa, Ram; Bandikatla, Sudeepthi V.; Chen, Dung-Tsa; Hicks, J. Kevin; Gray, Jhanelle E.; Puri, Sonam (Frontiers in Oncology, 2025)
BackgroundOncogenic BRAF mutations affect ~4% of non-small cell lung cancer (NSCLC). Class I mutations (i.e., V600) are typically responsive to BRAF/MEK inhibitors, while non-Class I are often resistant. The role of immune checkpoint inhibitors (ICIs) as first-line therapy in BRAF-mutant NSCLC remains unclear.MethodsWe retrospectively analyzed patients with BRAF-mutant NSCLC treated at Moffitt Cancer Center from January 1, 2012, to August 9, 2023. Demographics, biomarker (e.g., PD-L1, molecular profile), and treatment data were collected. Progression-free survival (PFS) and overall survival (OS) were estimated using standardized real-world endpoints.ResultsAmong 122 individuals, 54 had Class I and 68 had non-Class I mutations. For Class I mutations, ICIs yielded a PFS of 9.2 months and OS of 42.2 months, representing a significant OS advantage over chemotherapy-alone (22.2 months; p = 0.03). Outcomes were comparable to those seen with anti-BRAF/MEK therapy (PFS 14.7 months; p = 0.49, OS NE; p = 0.99), while ICIs trended towards improved OS in those with PD-L1 ≥50% (53.1 vs. 24.8 months; p = 0.61). For non-Class I mutations, ICI benefit was more limited (PFS 11.7 months, OS 18.5 months) yet compared favorably to chemotherapy-alone (PFS 4.7 months; p = 0.01; OS 9.9 months; p = 0.22). No patients with non-Class I mutations received anti-BRAF/MEK therapy.ConclusionICIs appear effective in BRAF mutant-NSCLC. For Class I mutations, ICIs yielded significant survival benefit over chemotherapy-alone. Outcomes were comparable to anti-BRAF/MEK therapy, with a potential survival advantage favoring ICIs in those with PD-L1 ≥50%. For non-Class I mutations, ICIs benefit was more modest but compared favorably to chemotherapy-alone.